Major acute cardiovascular events after dengue infection–A population-based observational study - Wei, Kai-Che; Sy, Cheng-Len; Wang, Wen-Hwa; Wu, Chia-Ling; Chang, Shang-Hung; Huang, Yu-Tung (PLoS neglected tropical diseases, 2022)
Dengue virus (DENV) infection may be associated with increased risks of major adverse cardiovascular effect (MACE), but a large-scale study evaluating the association between DENV infection and MACEs is still lacking. All laboratory confirmed dengue cases in Taiwan during 2009 and 2015 were included by CDC notifiable database. The self-controlled case-series design was used to evaluate the association between DENV infection and MACE (including acute myocardial infarction [AMI], heart failure and stroke). The "risk interval" was defined as the first 7 days after the diagnosis of DENV infection and the "control interval" as 1 year before and 1 year after the risk interval. The incidence rate ratio (IRR) and 95% confidence interval (CI) for MACE were estimated by conditional Poisson regression. Finally, the primary outcome of the incidence of MACEs within one year of dengue was observed in 1,247 patients. The IRR of MACEs was 17.9 (95% CI 15.80-20.37) during the first week after the onset of DENV infection observed from 1,244 eligible patients. IRR were significantly higher for hemorrhagic stroke (10.9, 95% CI 6.80-17.49), ischemic stroke (15.56, 95% CI 12.44-19.47), AMI (13.53, 95% CI 10.13-18.06), and heart failure (27.24, 95% CI 22.67-32.73). No increased IRR was observed after day 14. The risks for MACEs are significantly higher in the immediate time period after dengue infection. Since dengue infection is potentially preventable by early recognition and vaccination, the dengue-associated MACE should be taken into consideration when making public health management policies.